Antibacterial Activity of Bajakah Tampala (Spatholobus littoralis Hassk.) Methanol Extract in Roll-On Deodorant against Staphylococcus epidermidis - Dwisari, Fath; Dermawan, Abdurraafi' Maududi; Rahma, Nur Atika; Tjoadri, Tessa Nathalia; Abidin, Khoirul Rista (Jurnal Mandala Pharmacon Indonesia, 2025)
Body malodor results from the bacterial breakdown of apocrine gland secretions, with Staphylococcus epidermidis identified as a key contributor. Conventional deodorants often rely on synthetic compounds that may cause skin irritation or pose long-term health risks. This study aimed to formulate and assess an antibacterial roll-on deodorant containing methanolic extract of Spatholobus littoralis Hassk., a Kalimantan-native medicinal plant known for its antibacterial properties. The extract, prepared via maceration, was incorporated into a multiphase emulsion base comprising zinc ricinoleate, aluminum potassium sulfate, Carbopol 940, triethanolamine, Lexemul CS20, BHT, and phenoxyethanol. The formulations were evaluated for their physicochemical characteristics—pH, spreadability, adhesiveness, and homogeneity—as well as antibacterial activity against S. epidermidis using the disc diffusion assay. The extract-containing formulations (F1–F3) exhibited a beige color, herbal aroma, and uniform texture. The pH values (4.12–4.35) were within the dermally acceptable range. The spreadability varied from 4.59 to 4.81?cm, while the adhesiveness ranged from 0.34?s to 5.25?min, indicating favorable application and retention properties. Antibacterial testing showed inhibition zones of 10.40–12.37?mm, comparable to a commercial control (p?>?0.05). These findings suggest that S. littoralis extract is a potential natural, skin-compatible antibacterial agent for topical deodorant applications